ACADEMIC SELF-CONCEPT ON READING COMPREHENSION - Impiani Zagoto (Institut Pendidikan Tapanuli Selatan, 2020)
This study aims at looking for the correlation between reading comprehension and academic self-concept. This is a quantitative correlational design. The data of this study was gathered through questionnaire and test. The questionnaire was used to get the data of the students’ academic self-concept and the test to get the students reading comprehension. The Pearson Product Moment correlation was used to find out the significance relation between students’ academic self-concept and reading comprehension. Based on the data analysis, it is found that there is significant correlation between students’ academic self-concept and students reading comprehension since r count (0,49) was higher than r table (0, 413). Then, the coefficient determination was 0,24. In other words, the academic self-concept of the students helps students to comprehend the reading text well.